The case for a standard model description for process simulation. (2nd June 2005) - Seila, Andrew F.
Over the past forty years, simulation and process modelling has progressed from a new research technique to a standard tool for system analysis that is used by thousands of professionals worldwide. The practice of process modelling is characterised by numerous vocabularies and model representations. Using an analogy to architectural modelling, this paper presents the case for a common, standards-based model representation that is needed to create the environment where simulation and process modelling will be used routinely to analyse system performance prior to system implementation or modification. The standard model description should minimally include a discrete event simulation modelling ontology, an XML standard for describing the structure of process models and a graphical representation.